Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi terhadap Kepuasan Kerja Guru SMK Negeri 2 Balikpapan - Nisa Ulkarima; Didik Hadiyatno; Tutik Yuliani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of work environment, work discipline and motivation on job satisfaction of teachers of SMK Negeri 2 Balikpapan. This research method is quantitative with the determination of the number of samples in this study using purposive sampling with ASN criteria as many as 73 people. Data were collected through interviews, and Likert scale based questionnaires. Data analysis was conducted using SEM-PLS with Smart-PLS and SPSS applications. The outer model was tested for construct validity and reliability, while the inner model measured the relationship between variables with the R-square value and the t-statistic hypothesis test. The results show the composite reliability and Cronbach’s Alpha values averaged above 0.70, indicating good reliability. The R-square value of 0.796 or 79.6% shows that the variables of work environment, work discipline, and motivation on job satisfaction are 0.786 or 78.6%. Hypothesis testing shows that work environment, work discipline and work motivation have a significant effect on job satisfaction with a p-value <0.05. Based on the results of the study, it is recommended to be able to maintain a good work environment, work discipline and work motivation in order to increase employee job satisfaction.